Legitimasi Penafsiran DI/TII Sensen Komara tentang Perubahan Arah Kiblat: Analisis Penafsiran QS. Al-Baqarah 142-144 - Hafid Nur Muhammad; Tasya Sekardila; Tia Dahtiana (Universitas Darussalam Gontor, 2025)
Interpretations with pragmatic and ideological approaches to Qur'anic verses have the potential to trigger deviations in people's understanding. Sensen Komara uses this interpretation to strengthen the ideology and legitimacy of his movement, which has the potential to cause division among Muslims. This study aims to analyze the methods and approaches used by Sensen Komara to examine the legitimacy of Sensen Komara's interpretation of the change in Qibla direction contained in QS. Al-Baqarah verse 142-144, as well as comparing it with authoritative interpretations from leading scholars. The research conducted is library research, namely by collecting library data. This research uses a qualitative-descriptive-analytical method by explaining or describing through clear words and detailing systematically, factually and accurately based on existing data. The interpretation of QS. Al-Baqarah 142-144 by DI/TII Sensen Komara reflects an attempt to use the Qur'an as a means of legitimizing the ideology of their movement. This pragmatic and ideological approach shows the courage to adapt the sacred text according to the context of their struggle. Interpretations that tend to be partial and contextually limited risk ignoring the universal and inclusive dimensions of Qur'ānic verses. As a consequence, the deep spiritual message of changing the Qibla direction as a symbol of Muslim obedience and unity can be reduced to a mere political tool. This interpretation shows the importance of a balance between understanding the historical context and the universal message of the Qur'an